OPTIMIZATION OF PIT SLOPE DESIGN AT BANKO BARAT PIT 2 IN 2016, PT BUKIT ASAM (PERSERO) TBK, TANJUNG ENIM MINING UNIT, SOUTH SUMATRA PROVINCE - Hulwani, Zati; Alam, Pocut Nurul; Al-Huda, Nafisah; Rusydy, Ibnu (Jurnal Sains dan Teknologi Reaksi, 2025)
Slope stability is generally a critical concern in maintaining daily mining operations, as instability can disrupt activities and result in material losses or even fatalities. In designing an open-pit mine, it is essential to conduct slope stability analysis to ensure both safety and economic efficiency. This study focuses on optimizing slope stability analysis at PT Bukit Asam (Persero) Tbk, specifically in the Banko Barat Pit 2 area, using the Bishop Simplified method. The analysis was conducted using GeoSlope 2007/Slope W software to design and optimize a safe excavation slope by incorporating secondary data obtained from PT Bukit Asam, including mining design parameters (slope geometry) and the physical and mechanical properties of the rock, such as density, cohesion, and internal friction angle. The optimization results indicated that cross-sections A-A', C-C', and D-D' could accommodate an additional 3 benches. Cross-section B-B' was also optimized by adding 3 benches downward. The safety factor (SF) values for the first and second optimization scenarios showed stable slope conditions. However, for the third optimization (overall slope), the SF values indicated a marginal or risky condition. Cross-section E-E' could be optimized by adding 5 benches downward, and all five cross-sections remained in a stable condition. Keywords: Safety Fctor, Slope Stability, Bishop Simplified Method, Optimization, GeoSlope 2007/Slope W software